Distribusi Kekayaan Yang Adil Perspektif Dari Al-Qur'an - Andriano, Beni; Mahfuz , Taufik Warman; Noor, Syamhudian (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The study employs a qualitative approach using a literature review method to analyze relevant Qur'anic verses and hadiths concerning wealth distribution. Primary data were sourced from Qur'anic interpretations, Islamic economic literature, and other supporting references such as books and journal articles discussing distribution in Islam. The analysis was conducted descriptively to identify the principles of distribution outlined in Islam and their implications for social justice. Data validity was ensured through source triangulation from credible references to guarantee accuracy and depth of information.The analysis reveals that wealth distribution is a crucial element in Islamic economics to achieve social and economic balance. This research explores the concept of distribution from the perspective of the Qur'an, focusing on principles of social justice, distribution instruments such as zakat, infak, and sedekah, and the prohibition of wealth accumulation. The study highlights how Qur'anic verses direct the management of wealth to prevent its concentration among a select few and ensure equitable distribution across society. Through this study, it is found that economic distribution in Islam contributes to reducing economic disparities, enhancing social solidarity, and promoting overall societal stability.